PENOLAKAN LOCKHEED MARTIN TERHADAP PENJUALAN JET TEMPUR F-35 KE TURKI - Bustami, Sirwan Yazid; Zulkarnain, Zulkarnain; Suardana, I Ketut; Rezkita, M. Ridho (Department of International Relations Universitas Satya Negara Indonesia, 2025)
The research aims to analyze the factors influencing Lockheed Martin’s rejection of the sale of the F-35 JSF Fighter Jet to Turkey. The influential factors were examined using a single instrumental-explanatory case study research method. This method provides an in-depth understanding of Lockheed Martin’s decision by analyzing the causal relationships between variables based on the theory of the interests of the home country of multinational corporations and the theory of the nexus of contracts. Data were collected through a literature review and analyzed through several stages, including the selection of themes, topics, and cases; literature reading; formulation of research focus and problems; data collection; data refinement; data processing; data analysis; theoretical dialogue; and conclusion of research results. Based on the findings, Lockheed Martin’s rejection of the sale of the F-35 JSF Fighter Jet to Turkey was influenced by United States national security factors, compliance with the CAATSA sanctions regime, and reputational risk threats.